2019
DOI: 10.1080/20013078.2019.1597614
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from N‐Myc amplified neuroblastoma cells induce migration and confer chemoresistance to non‐N‐Myc amplified cells: implications of intra‐tumour heterogeneity

Abstract: Neuroblastoma accounts for 15% of childhood cancer mortality. Amplification of the oncogene N-Myc is a well-established poor prognostic marker for neuroblastoma. Whilst N-Myc amplification status strongly correlates with higher tumour aggression and resistance to treatment, the role of N-Myc in the aggressiveness of the disease is poorly understood. Exosomes are released by many cell types including cancer cells and are implicated as key mediators in cell-cell communication via the transfer of molecular cargo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 32 publications
1
64
0
Order By: Relevance
“…The present study provides an additional mechanistic insight into the ability of OV to suppress OSCC tumorigenesis by reducing the cargo of CSC-derived EVs. OV treatment suppressed the self-renewal capability of CAL27 and SCC-15 cells and reduced the cargo within EVs generated from CSCs, highlighting the therapeutic potential of OV, since EV cargos are considered one of the major routes for cancer cells to communicate with each other and with the TME [42,43]. It is also relevant that OV treatment significantly reduced the miR-21-5p level within CSC_EVs alongside STAT3 and mTOR, especially as evidence abounds that increased miR-21 levels in breast cancer cells are associated with inhibition of tumor suppressors, such as PDCD4 and PTEN, coupled with amplification of mTOR signaling and promotion of CAF transformation via suppression of Smad7 [18,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides an additional mechanistic insight into the ability of OV to suppress OSCC tumorigenesis by reducing the cargo of CSC-derived EVs. OV treatment suppressed the self-renewal capability of CAL27 and SCC-15 cells and reduced the cargo within EVs generated from CSCs, highlighting the therapeutic potential of OV, since EV cargos are considered one of the major routes for cancer cells to communicate with each other and with the TME [42,43]. It is also relevant that OV treatment significantly reduced the miR-21-5p level within CSC_EVs alongside STAT3 and mTOR, especially as evidence abounds that increased miR-21 levels in breast cancer cells are associated with inhibition of tumor suppressors, such as PDCD4 and PTEN, coupled with amplification of mTOR signaling and promotion of CAF transformation via suppression of Smad7 [18,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic exclusion was programmed to be 30 sec. For SILAC‐based mass spectrometry, LC‐MS/MS was carried out on a LTQ Orbitrap Elite (Thermo Scientific) with a nanoelectrospray interface coupled to an Ultimate 300 RSLC nanosystem (Dionex) as described previously [25].…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes from cell lines derived from primary tumors (IMR32 and IGR-NB8) contain a higher level of proteins involved in ECM assembly and adhesion, as well as in neuronal development, whereas exosomes isolated from cell lines derived from bone marrow metastasis (SK-N-SH, SH-SY5Y, IGR-N91, SK-N-BE(2)-C, and LAN-1) contain proteins that are associated with cell survival, proliferation and motility [ 84 ]. Proteomic analysis performed on exosomes from two NB cell lines with different MYCN amplification status reflects their role in the aggressiveness of NB, as exosomes from MYCN-A SK-N-BE(2) cells are enriched in proteins involved in signal transduction, cell communication and transport, while exosomes from MYCN-NA SH-SY5Y are enriched in protein metabolism, cell growth, and maintenance and regulation of nucleic acid metabolism, suggesting that SK-N-BE2 cell-derived exosomes are enriched with proteins that could regulate various signaling pathways in the recipient cells [ 85 ]. More recently, a mass spectrometry-based proteomic profiling study of EVs isolated from plasma of NB patients, compared to healthy controls, has led to the identification of a NB specific signature including ferritin heavy chain (FHC), keratin, type I cytoskeletal 17 (KRT17), histone H3.3 (H3F3A), ATP binding cassette sub-family B member 9 (ABCB9), a disintegrin and metalloproteinase with thrombospondin motifs 13 (ADAMS13), CD14, erythrocyte membrane protein band 4.2 (EPB42), hepatocyte growth factor activator (HGFAC), keratin, type I cytoskeletal 13 (KRT13), and KRT8, all proteins related to cell proliferation and differentiation [ 86 ].…”
Section: Evs and Mirs New Mechanisms Of Communication Between Nbmentioning
confidence: 99%
“…Our understanding of the mechanisms involved in these multiple interactions in NB is so far limited and primarily derived from in vitro co-culture experiments. Several studies have shown that EVs play a role in tumor cell to tumor cell communications, affecting the cells phenotype, their migratory potential, or conferring chemoresistance [ 85 , 91 ]. We also demonstrated that NB-derived EVs contribute to the communication between tumor cells and stromal cells, showing that exosomes derived from NB cells induced in vitro the production of pro-tumorigenic cytokines and chemokines such as IL-6, IL-8, VEGF, and CCL2 by MSCs [ 92 ].…”
Section: Evs and Mirs New Mechanisms Of Communication Between Nbmentioning
confidence: 99%